Model keunggulan bersaing UMKM kerajinan anyaman bambu di Bali - I Made Kartika; I Made Sumada; I Made Adi Suwandana; Dewa Gede Putra Sedana; Putu Gede Denny Herlambang; Yudistira Adnyana; I Gusti Bagus Rai Utama (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The COVID-19 pandemic has affected all business sectors, including micro, small and medium enterprises (MSMEs). One of the MSMEs affected is the bamboo handicraft MSME in Bali. However, currently economic conditions are starting to rise. MSMEs must formulate new strategies to improve their competitiveness. Based on this review, this study aims to explore these aspects in depth to build the competitive advantage of bamboo plaiting MSMEs in Bali. In addition, this study also describes the supporting and inhibiting factors in increasing the competitive advantage of bamboo woven MSMEs in Bali in terms of the use of raw materials, production processes, and marketing strategies. This research includes descriptive qualitative research with data collection techniques through interviews. The research informants were 10 bamboo weaving craftsmen in Buleleng, and Bangli Regencies. The data analysis technique used qualitative data analysis. The results concluded that the competitive advantage model of bamboo plaiting MSMEs in Bali was built through 3 elements, namely raw materials (adequacy of raw materials, planning planting and harvesting time, selection of raw materials, use of quality raw materials), production processes (maintaining handmade, innovation, use of drying machines), and marketing strategies (improving network quality, participating in digital marketing training, and using online marketing strategies).